Optical soliton solutions for generalized NLSE using Jacobi elliptic functions - İnç, Mustafa; Ates, Esma (Natl Inst Optoelectronics, 2015)
In this paper, the generalized NLSE is studied with four forms of nonlinearity. The Jacobi elliptic functions are used to obtain exact solutions of this equation. Bright and dark optical soliton solutions are also retrieved for the generalized NLSE.
Keywords: NLSE; Jacobi elliptic functions; Optical soliton solutions